Pengaruh Praktik Human Capital Performance Management (HCPM) dan Work Engagement terhadap Peningkatan Kinerja Pegawai Swasta Generasi Z di Kota Bima - Jaenab; Sugeng Widakdo; Mulyadin (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
The purpose of this study is to determine the simultaneous positive and significant influence of Human Capital Performance Management (HCPM) and work engagement on the performance of Generation Z employees in Bima City. This research employs a quantitative approach. The type of research used is associative, with the population consisting of all private-sector Generation Z employees in Bima City. The sample includes 100 Generation Z employees selected through purposive sampling based on specific criteria. The research instrument used is a questionnaire with a Likert scale. The data analysis technique applied in this study is multiple linear regression analysis using SPSS version 21. The results of the study show that: (1) Human Capital Performance Management (HCPM) has a positive and significant effect on the performance of Generation Z employees in Bima City; (2) Work engagement has no positive and significant effect on the performance of Generation Z employees in Bima City; and (3) Human Capital Performance Management (HCPM) and work engagement jointly have a positive and significant effect on the performance of Generation Z employees in Bima City